Mokhtar Dahari the Malaysia football legend / Mohamad Hanif Abd. Manaf - Abd. Manaf, Mohamad Hanif (2014)
It have been 30 years, Malaysia football were poor in every kind of aspect such as facilities, style of play, referee and many more. Although football is the country number one sport, their performance these past years made Malaysia football lags behind other Asians country such as Japan, Korea, Australia even Thailand. Why could this happen? Where are the gold era of Malaysia that had achieved in the 1970's? Are Malaysia lack of good players such as Soh Chin Aun, Ghani Minhat or Mokhtar Dahari? In that case, youngsters nowadays did not know about Malaysia football and especially the gold era of Malaysia football and more importantly about Mokhtar Dahari. It's a bit embarassing Malaysian youngsters did not appreciate Malaysian players. Mokhtar Dahari were one of the best players in Malaysia and, Asia. Youngsters nowadays need to know Mokhtar Dahari and commemorate him and make him as a an icon in daily life. Mokhtar Dahari way of achieving goals can be example to youngsters to achieve theirs also.